2013
DOI: 10.1161/strokeaha.113.000990
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran Versus Warfarin

Abstract: Background and Purpose— Intracranial hemorrhage rates are higher in Asians than non-Asians, especially in patients receiving warfarin. This randomized evaluation of long-term anticoagulation therapy subgroup analysis assessed dabigatran etexilate (DE) and warfarin effects on stroke and bleeding rates in patients from Asian and non-Asian countries. Methods— There were 2782 patients (15%) from 10 Asian countries and 15 331 patients from 34 non-Asian count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 292 publications
(112 citation statements)
references
References 16 publications
3
106
1
2
Order By: Relevance
“…Dabigatran with 110 mg twice daily was the only low‐dose NOAC that was independently compared with warfarin among the 3 pivotal NOAC studies 2. The Asian subgroup analysis from the RE‐LY trial (Randomized Evaluation of Long‐Term Anticoagulation Therapy) indicated that low‐dose dabigatran caused a similar risk of thromboembolic events (HR, 0.82; 95% CI, 0.55–1.24) and a significantly lower risk of major bleeding (HR, 0.57; 95% CI, 0.38–0.86) compared with warfarin 29. Our findings in ≈88% of patients taking low‐dose dabigatran in Taiwan are in line with the findings from the RE‐LY trial, with lower risks of thromboembolic events (HR, 0.82; 95% CI, 0.68–0.98) and major bleeding (HR, 0.65; 95% CI, 0.53–0.80) for dabigatran versus warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…Dabigatran with 110 mg twice daily was the only low‐dose NOAC that was independently compared with warfarin among the 3 pivotal NOAC studies 2. The Asian subgroup analysis from the RE‐LY trial (Randomized Evaluation of Long‐Term Anticoagulation Therapy) indicated that low‐dose dabigatran caused a similar risk of thromboembolic events (HR, 0.82; 95% CI, 0.55–1.24) and a significantly lower risk of major bleeding (HR, 0.57; 95% CI, 0.38–0.86) compared with warfarin 29. Our findings in ≈88% of patients taking low‐dose dabigatran in Taiwan are in line with the findings from the RE‐LY trial, with lower risks of thromboembolic events (HR, 0.82; 95% CI, 0.68–0.98) and major bleeding (HR, 0.65; 95% CI, 0.53–0.80) for dabigatran versus warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be that it was the selection of few patients with high risk among the AC‐treated men (Kim et al., 2011). The observation period of the patients with CE cerebral infarction in this trial could not be compared with NOAC trials in which the mean and median observation times were only between 1 and 2 years (Alberts et al., 2012; Diener et al., 2012; Hankey, 2014; Hori et al., 2013; Lopes et al., 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Due to the verified beneficial effects of NOACs in patients with AF compared with warfarin (Alberts et al., 2012; Diener et al., 2012; Hankey, 2014; Hori et al., 2013; Lopes et al., 2012) and the observation in the present trial of a higher annual risk of death during treatment with APT versus AC in men compared with women, this trial supported studies evaluating NOACs, especially in male patients with arterial thromboembolism or myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sub‐analysis in Japanese patients from the Randomized Evaluation of Long‐term anticoagulant therapY (RE‐LY) trial indicated similar safety and efficacy for DE vs warfarin and higher bleeding rates for warfarin in Asians vs non‐Asians6, 7; this was attributed to postulated genetic differences in blood coagulation between Asian and non‐Asian subjects. The reductions in hemorrhagic stroke and major bleeding rates were comparable between Asians vs non‐Asian patients treated with DE 8…”
Section: Introductionmentioning
confidence: 99%